ИНТЕРНЕТ-ЛИНГВИСТИКА И ЯЗЫКИ, ОБЕСПЕЧИВАЮЩИЕ ЭЛЕКТРОННЫЕ СРЕДСТВА КОММУНИКАЦИИ - Кененбаев, Е.Т. (SCIENCE and SOCIETY, 2024)
The subject of this study was various electronic means of information transmission, which together form a special language that serves the communication of the Internet information field.
Keywords: Internet; linguistics; communication; electronic media; languages